The prevalence of burnout among oncology professionals: oncologists are at risk of developing burnout - Eelen, S.; Bauwens, S.; Baillon, C.; Distelmans, W.; Jacobs, E.; Verzelen, A. (Psycho-oncology (Chichester, England), 2014)
Objective International research shows that oncology staff suffers more from burnout than other healthcare professionals. Burnout is common among oncologists. The prevalence of emotional exhaustion, depersonalization, and low personal accomplishment appears to be significantly higher among physicians. Detecting burnout is highly relevant, because it affects the personal well‐being and quality of life of the healthcare professional. A national study on the prevalence of burnout in oncology was never conducted in Flanders (Dutch‐speaking part of Belgium). Methods The Cédric Hèle institute spread anonymous questionnaires among 923 healthcare workers in oncology (physicians, social workers, psychologists, nurses, and specialist‐nurses) in Flanders. The questionnaire consisted of two parts. The first part contained questions concerning demographic and job features. The second part included the Dutch version of the Maslach Burnout Inventory. Results Five hundred and fifty subjects participated in the survey (response rate of 59.5%). Of the medical oncologists, 51.2% suffered from emotional exhaustion, 31.8% from depersonalization, and 6.8% from a lack of personal accomplishment. Multivariate analysis of variance suggested a significantly elevated level of emotional exhaustion and depersonalization in oncologists compared with other professionals. Logistic regression indicated that the following variables have predictive value on risk of burnout: gender, profession, and combining work in a university hospital with work in a private hospital. Conclusion The CHi research showed a significantly increased level of burnout‐components in professionals working in oncology, especially in medical oncologists. These results should have an impact on the daily clinic of oncology, and could be guidance for further research. Copyright © 2014 John Wiley & Sons, Ltd.